2019
DOI: 10.1002/jor.24406
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell‐derived extracellular vesicles attenuate the early inflammatory response after tendon injury and repair

Abstract: Adipose‐derived stem cells (ASCs) have the potential to enhance tendon repair via paracrine regulation of the inflammatory response to injury. Extracellular vesicles (EVs), which are secreted by ASCs, have shown promise in mediating this process. This study was designed to evaluate the effect of ASC EVs on early tendon healing using a mouse Achilles tendon injury and repair model. EVs were isolated from the conditioned medium of naïve and interferonγ‐primed ASCs and applied to the repair site via a collagen sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
164
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(173 citation statements)
references
References 39 publications
2
164
0
Order By: Relevance
“…Higher concentrations of MSC-derived EVs performed better than low concentrations and better than MSCs alone. As already shown [9,10,11], three studies have already been published on this topic, but direct comparisons with the present investigations are difficult given the different focus. The three previous studies focused largely on inflammatory mechanisms, and used different methodologies and different types of injury over different time periods.…”
Section: Plos Onementioning
confidence: 66%
See 1 more Smart Citation
“…Higher concentrations of MSC-derived EVs performed better than low concentrations and better than MSCs alone. As already shown [9,10,11], three studies have already been published on this topic, but direct comparisons with the present investigations are difficult given the different focus. The three previous studies focused largely on inflammatory mechanisms, and used different methodologies and different types of injury over different time periods.…”
Section: Plos Onementioning
confidence: 66%
“…Cell-free delivery of bioactive cargos by EV induces the same beneficial responses as stemcell transplantation, offering remarkable benefits over conventional cell-therapy: for example, EVs avoid the risk of tumorigenesis, and heterotopic ossification and calcification [3,4] and are immunologically unresponsive agents [7,8]. Finally EVs play a role in tendon-healing by modulating inflammatory responses [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of tenocytes in a number of in vitro and in vivo experimental models with EVs from various sources, e.g. plasma [ 14 ], adipose stem cells [ 15 ], tendon progenitors [ 16 ], macrophages [ 17 ], have demonstrated that signalling through EVs can modulate the expression of genes that regulate ECM synthesis and remodelling. Exosomes derived from tendon cells have also been reported [ 18 , 19 ]; and one study showed that tendon cell-derived exosomes induce the expression of tenogenic genes in bone marrow-derived mesenchymal stem cells in a TGFβ-dependent manner [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…EVs also have the potential to enhance tendon repair via paracrine regulation of the inflammatory response to injury [154]. In a model of Achilles tendon healing after unilateral surgical transection, AD-MSC EVs were loaded to the surface of a collagen sheet which was applied around the repair site.…”
Section: Skeletal Muscle and Tendon Repairmentioning
confidence: 99%
“…In a model of Achilles tendon healing after unilateral surgical transection, AD-MSC EVs were loaded to the surface of a collagen sheet which was applied around the repair site. This treatment attenuated inflammatory cell migration and NF-κB activation whereas the anabolic response was facilitated leading to tendon matrix regeneration [154]. Another possible strategy consists of polarizing macrophages to an M2 phenotype by incubating these cells with EVs from human BM-MSCs.…”
Section: Skeletal Muscle and Tendon Repairmentioning
confidence: 99%